2021
DOI: 10.21203/rs.3.rs-824580/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibiting α1-adrenergic Receptor Signaling Pathway Ameliorates Alzheimer’s Disease Type Pathologies and Behavioral Deficits in an AD Mouse Model

Abstract: Background The role of α1 adrenergic receptors (α1-ARs) signaling pathway in the pathogenesis of Alzheimer’s disease (AD) has rarely been investigated. Clarifying pathophysiological functions of α1-ARs in the AD brain is helpful for better understanding the pathogenesis and screening novel therapeutic target of AD. Methods This study included 2 arms of in vivo investigations: 1) 6-month-old female APPswe/PS1 mice were intravenously treated with AAV-PHP.eB-shRNA (ARs)-GFP or AAV-PHP.eB-GFP for 3 months. 2) 3-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…124 Additionally, knockdown of α1-adrenergic receptors lessened brain amyloid burden and specifically the α1-adrenergic receptor inhibitor, terazosin, significantly decreased Aβ deposition and attenuated hyperphosphorylation of tau, glial activation, neuronal death, and synaptic dysfunction. 124 It has been found that the expression of α1adrenergic receptors is preserved in the cerebrovasculature within the aging population and in individuals that have CAA, further supporting the feasibility of using α1-adrenergic antagonists to combat dementia related vascular pathology. 125 Not many studies have investigated how drugs that target the α2-adrenergic system affect AD pathology.…”
Section: Adrenergic Drugs and Reduction Of Ad Risk And Pathologymentioning
confidence: 98%
See 2 more Smart Citations
“…124 Additionally, knockdown of α1-adrenergic receptors lessened brain amyloid burden and specifically the α1-adrenergic receptor inhibitor, terazosin, significantly decreased Aβ deposition and attenuated hyperphosphorylation of tau, glial activation, neuronal death, and synaptic dysfunction. 124 It has been found that the expression of α1adrenergic receptors is preserved in the cerebrovasculature within the aging population and in individuals that have CAA, further supporting the feasibility of using α1-adrenergic antagonists to combat dementia related vascular pathology. 125 Not many studies have investigated how drugs that target the α2-adrenergic system affect AD pathology.…”
Section: Adrenergic Drugs and Reduction Of Ad Risk And Pathologymentioning
confidence: 98%
“…Tamsulosin, another antagonist of the α1‐adrenergic receptor, has recently been found to improve age‐related memory impairment in rats due to increased hippocampal neurogenesis and prevention of apoptosis within the hippocampus 123 . An even more recent study demonstrated that knockdown of α1‐adrenergic receptors within APP/PS1 AD mice improved performances on y‐maze, open field test, Morris water maze, and elevated plus maze 124 . Additionally, knockdown of α1‐adrenergic receptors lessened brain amyloid burden and specifically the α1‐adrenergic receptor inhibitor, terazosin, significantly decreased Aβ deposition and attenuated hyperphosphorylation of tau, glial activation, neuronal death, and synaptic dysfunction 124 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation